The design of the chinese canoeing team training information management platform (CCIMP) - Sun, J. H.; Yi, C.; Ma, Y. C.; Cao, L.; Li, X. C.; Cao, J. W. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
Utilizing the theory and methods of system engineering and on the basis of the national canoeing team's demand, we tentatively design and develop the first Chinese canoeing information management platform (CCIMP) system of water events and realize the integration of decision-making, intelligent management and scientific training. The system also has the butt and interactive function between a scientific network of the training platform and a special information platform. It helps to solve the problems of training competition management, training diary, training plan, physiological and technical test, intelligent analysis and process of training test data and injury management, and achieves effective control over the training process of the national canoeing team.